Experience of sexual harassment in patients with mental disorders - Sukarni; Siti Nurjanah (UM Purwokerto Press, 2020)
Sexual harassment is a form of an unpleasant experience making a person uncomfortable. It has physical or psychological impacts. 163-403-2-ED. The research aimed to find out the experience of sexual harassment that causes behavioral changes in patients with mental illness in Banyumas Regional Hospital.This was quantitative descriptive research. There were 32 people taken as the research sample using purposive sampling technique. The data resulted in the distribution of each variable in percentage, classified in the Slovin formula. A questionnaire from the Sexual Harassment Inventory (SHI) was also employed. The average age of the patients who had experienced sexual harassment was 31.53 years, and it happenned when they were 19.56 years. Most of them were male (68.8%), had primary school education (40.6%), and were already employed (53, 1%). The sexual harassment was in the form of verbal and non-verbal abuse (59.4%). It mostly occurred 1-2x (40.6%) in patients with a history of mental care 1-3x (40.6%). The perpetrators were mostly female (59.4%) and non-family members (87.5%). Most of the patients experienced severe sexual harassment (84.4%), causing annoyance (46.9%).In conclusion sexual harassment can be a factor in mental illness.